Examining the efficacy of dance movement and music mixed treatment on social communication impairment in children with autism — Based on family parent-child situation - Ren, Huiting; Ren, Guanghao; Zhan, Yuqi; Jia, Zhichun (Frontiers in Psychology, 2022)
Despite impairments in social communication in children with autism spectrum disorder (ASD), existing studies only examine the effects of either MT or DMT interventions. In the family setting, few studies have investigated interventions for social communication impairments in children with ASD. This study designed and tested a mixed intervention program of both MT and DMT through a 3-month intervention and training for children with ASD in the family setting including parent and child. A pre-test and post-test were conducted in the experimental and control groups, and the childhood autism rating scale (CARS) and autism treatment evaluation checklist (ATEC) scales were used to assess the severity of ASD symptoms and the effects of intervention. A t-test and analysis of variance were performed based on the experimental results. The results indicated that the experimental and control groups did not differ significantly on the CARS pre-test (t = 1.218, p > 0.05) and that there was no significant difference in the ATEC pre-test (t = 0.546, p > 0.05; F = 0.074, p > 0.05, partial η2 = 0.003). There was no significant difference between the pre- and post-test scores for the CARS in the control group (t = 0.635, p > 0.05), and there was no significant difference between the pre- and post-test scores for the ATEC in the control group (t = 0.027, p > 0.05; F = 5.251, p > 0.05, partial η2 = 0.313). There was a significant difference between the pre- and post-test scores on the CARS in the experimental group (t = 4.327, p > 0.05) and the pre- and post-test scores on the ATEC in the experimental group (t = 5.763, p > 0.01; F = 32.615, p > 0.01, partial η2 = 0.759), with the post-test scores being lower than the pre-test scores. This demonstrates that the mixed intervention of MT and DMT in the family parent-child setting can reduce autism and improve social communication impairment in children with ASD.